2017
DOI: 10.1016/j.adro.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic response after neoadjuvant chemotherapy predicts locoregional control in patients with triple negative breast cancer

Abstract: PurposeOur goal was to determine the impact of pathologic response after neoadjuvant chemotherapy in triple negative breast cancer (TNBC) on the subsequent risk of locoregional recurrence (LRR) and disease-free survival (DFS) in the setting of adjuvant radiation therapy.Methods and materialsThis was an institutional review board–approved retrospective chart review of patients with clinical stage I-III breast cancer treated with neoadjuvant chemotherapy, local surgery (breast conservation or mastectomy), and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 15 publications
2
24
0
2
Order By: Relevance
“…However, this analysis encompassed all subtypes of breast cancers. In a TNBCspecific cohort of patients receiving NAC, surgery, and RT, Chen et al 12 reported that at 2-year follow-up, patients who experienced pCR had a 0% rate of LRR versus 27.5% in those who did not. This is similar to our findings, wherein patients who experienced pCR had a 0% rate of LRR versus 22% in those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…However, this analysis encompassed all subtypes of breast cancers. In a TNBCspecific cohort of patients receiving NAC, surgery, and RT, Chen et al 12 reported that at 2-year follow-up, patients who experienced pCR had a 0% rate of LRR versus 27.5% in those who did not. This is similar to our findings, wherein patients who experienced pCR had a 0% rate of LRR versus 22% in those who did not.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Moreover, patients that receive neo-adjuvant chemotherapy (NAC) have a low rate of complete pathological response (pCR), which ranges from 26.4% to 47.4%. [7][8][9][10] The standard criterion to assess response to NAC response is currently pCR. [11][12][13] New parameters as predictors of the prognosis of patients with breast cancer treated with NAC.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is the most common malignancy affecting women's health, with increasing incidence worldwide. About 1 in 8 women will be diagnosed with breast cancer in their lifetimes; moreover, 1 in 5 cases of breast cancer is the triple-negative subtype, that is, negative for estrogen receptor, progesterone receptor, and human epidermal growth factor receptor 2 (HER2) (1). Triple-negative breast cancer (TNBC) tends to be particularly aggressive, with a higher propensity for metastasis and locoregional recurrence compared with other subtypes (2).…”
Section: Introductionmentioning
confidence: 99%